2008
DOI: 10.1038/eye.2008.177
|View full text |Cite
|
Sign up to set email alerts
|

Ocular involvement is associated with HLA-B51 in Adamantiades–Behçet's disease

Abstract: Purpose To evaluate the association of HLA-B51 and ocular involvement in Adamantiades-Behçet's disease. Methods We retrospectively analysed all patients with Adamantiades-Behçet's disease examined in our Department of Ophthalmology since 1982. All patients fulfilled the criteria of the International Study Group for Behçet's disease. We included 140 patients (63 female and 77 male) with a mean follow-up of 6.4 years. Results The mean age at the first manifestation was 23 years; full disease was noted at 32 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 33 publications
3
10
0
2
Order By: Relevance
“…[13][14][15][16] Results of these studies partially support our findings, but they have not examined whether patients smoke or not. Bilgin et al 2 have also reported that cystoid macular edema among current smoking patients with BD was significantly higher than nonsmoking patients, but smoking was inefficient on other ocular involvement.…”
Section: Discussionsupporting
confidence: 80%
“…[13][14][15][16] Results of these studies partially support our findings, but they have not examined whether patients smoke or not. Bilgin et al 2 have also reported that cystoid macular edema among current smoking patients with BD was significantly higher than nonsmoking patients, but smoking was inefficient on other ocular involvement.…”
Section: Discussionsupporting
confidence: 80%
“…HLA-B51 was associated with ocular involvement in ABD in our study, as we have described in detail before [29].…”
Section: Discussionmentioning
confidence: 54%
“…In fact, the clinical manifestations of BD show large patient to patient variation even within the same ethnic group, particularly with respect to the distribution of organ involvement. Furthermore, studies that have investigated the association between HLA-B*51 and certain clinical subsets have suffered from limited statistical power and produced conflicting results [27][28][29][30][31][32][33][34][35][36][37][38] (Table 2). Nevertheless, ocular and cutaneous involvements have been frequently associated with HLA-B*51 in those studies that have presented positive results [27][28][29][31][32][33][34][35].…”
Section: Hla-b*51mentioning
confidence: 99%